INVESTIGATING TEXTUAL VARIANTS OF MARK 1:1 - Do Ngoc Hoa (Sekolah Tinggi Teologi Aletheia)
Abstract: This article revisits a classical case in textual criticism, textual variants of Mark 1:1. It presents all the variants from the available manuscripts and their respective dating. After that, it investigates all the variants using the textual criticism approach, focusing on the external and internal evidence. While affirming that this paper does not solve the problem since evidence for at least two readings is equally convincing, it concludes by confirming that the variant with longer reading is preferable and more likely to be the original. Abstrak: Artikel ini membahas kembali kasus klasik dalam studi Kritik Teks, yaitu berbagai variasi teks dalam Markus 1:1. Artikel ini memaparkan semua varian dari pelbagai manuskrip berserta dengan pentarikhannya masing-masing. Setelah itu, artikel ini menginvestigasi semua varian tersebut berdasarkan pendekatan Kritik Teks, dengan fokus pada bukti eksternal dan internal. Mengafirmasi bahwa kajian ini tidak menyelesaikan masalah tekstual dalam teks yang diselidiki karena bukti bagi kedua bacaan yang dominan sama-sama meyakinkan, artikel ini menyimpulkan bahwa varian dengan bacaan yang lebih panjang lebih meyakinkan dan kemungkinan besar asli.